Comparison of the effect of co-trimoxazole and co-trimoxazole plus ciprofloxacin in urinary tract infection prophylaxis in kidney transplant patients - Khorvash, Farzin (Adv Biomed Res, 2016)
BACKGROUND: Urinary tract infection (UTI) as an important infection in the setting of renal transplantation carries the high mortality and morbidity rate. Thus, the prevention of this infection should receive higher priority. However, bacterial resistance to antibiotics is on the rise, with limited data to guide prophylaxis. The purpose of this study was to compare the effect of sulfamethoxazole-trimethoprim (SMZ/TMP) and SMZ/TMP plus ciprofloxacin for prophylaxis of UTI in renal transplant recipients. MATERIALS AND METHODS: In a clinical trial study, 50 patients were included and divided into two groups of 25 using block randomization. Patients in Group I received prophylactic SMZ/TMP and those in Group II received ciprofloxacin plus SMZ/TMP. The incidence of UTI in the two groups at 1, 3, and 6 months after transplantation was evaluated. This study was registered in Iranian Registry of Clinical Trial (IRCT number: IRCT 2015120823743N1). RESULTS: Of the 61 patients older than 18 years at the time of transplantation, 50 were included. UTI was documented in 8 patients (32%) in Group I and 3 (12%) in Group II (P = 0.026). The average time for the development of the first case of infection was the same for both groups (P = 0.241), and it was at its maximum in the 1(st) month. Urinary infections caused by Escherichia coli, the dominant strain, were the same in both groups (P = 0.673). CONCLUSIONS: Our study shows that the addition of 1 month course of ciprofloxacin lowered the incidence of UTI. More studies are needed to confirm the efficacy of this approach.